Penanganan Rheumatoid Arthritis dengan Model Comfort Food for the Soul pada Lanjut Usia di Panti Werdha Kota Jambi - Hesty Hesty (Jurnal Abdimas Kesehatan (JAK), 2022)
The main complaint felt by patients with Rheumatoid Arthritis (RA) is pain that is very disturbing, affecting daily activities and quality of life. RA pain felt by the elderly has an impact, including making sufferers feel uncomfortable, often afraid to move for fear of severity so that it reduces productivity, disrupts body balance so that it is at risk for falling, becomes dependent on others and causes stress to sufferers. Pain experienced by a person is complex and is the result of the interaction of physiological, psychological factors, as well as the individual's past experience, context, and the benefits of the therapy he has undergone so far. Patients' perceptions of the pain they feel can also affect their behavior and affective responses, so an effective strategy is needed to deal with pain, emotional distress, and psychosocial barriers experienced. One form of intervention in the comfort food model for the soul can be done with religious music therapy. One of the management of RA is through the comfort food for the soul model. This community service activity was carried out at the Tresna Werdha Budi Luhur Social Home located on Jalan Pangeran Hidayat Paal V Kota Baru Jambi City in July 2020. The service method used a survey, lecture, discussion and demonstration approach. The results achieved were health education about Rheumatoid Arthritis, making education media posters, and booklets. 95% of the elderly understand how to treat Rheumatoid Arthritis pain. Comfort Food for the Soul model, .90% of moderate pain changes to mild pain.